PENGARUH INDIKATOR MAKROEKONOMI TERHADAP TINGKAT INFLASI DI ASEAN-5 - Annisa Yuliandari; Dini Hariyanti (Media Ekonomi, 2016)
This research aims to analyze the factors that influence Inflation towards ASEAN 5 countries, i.e. Indonesia, Malaysia, Singapore, Thailand, and Philippines 2000-2014. This research is using methods of analysis panel data to determine the factors the influence the Inflation inflows in ASEAN-5. The factors that influence Inflation are Money Supply, Interest Rate, Exchange Rate, and Gross Domestic Product. Based on the analysis panel data result shows that Money Supply and Gross Domestic Product have the negative and significant impact to Inflation in ASEAN-5. Interest Rate has a negative and significant impact to Inflation in ASEAN-5. Exchange Rate has a positive and not significant impact to Inflation in ASEAN-5.